Penerapan Lean Manufacturing Dengan Metode VSM (Value Sream Mapping) untuk Mengurangi Waste Pada Proses Produksi Pt.XYZ - andri andri; daniel sembiring (Faktor Exacta, 2018)
PT. XYZ is a company engaged in the sport shoe with the marketing areas inside and outside the country. One of the products produced by PT. XYZ is running shoes. The problems faced by the company is not achieving the production targets because many value-added activity not belonging to the waste (waste). For that use lean manufacturing approach to eliminate waste that occurs on in the production line at PT. XYZ. Lean manufacturing methods used is values stream mapping (VSM) to analyze the dominant waste in the manufacturing process. Based on the analysis we found three recommendations for improvement, namely the use of a forklift, the addition operator and addition of machine. Results of evaluation of recommendation is decreased production lead time equal to 8610.62 sec, increasing the value of Process Cycle Efficiency of 21.08%.